TRENDS AND RESEARCH LANDSCAPE OF THE FUZZY DELPHI METHOD: A BIBLIOMETRIC ANALYSIS (2015-2024) - Talib, Noor Husna; Abdullah, Mohammad Roshimi; Abdallah, Abdallah Saleh; Zolmaily, Muhammad Akmal; Zulkifli , Muhammad Firdhaus; Ku Yaakob, Ku Mohd Syarbaini (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The Fuzzy Delphi Method (FDM) has gained significant attention over the past decade as a structured expert consensus technique widely applied in multidisciplinary decision-making contexts. Despite its growing popularity, a comprehensive overview of its research landscape remains limited. This study aims to analyze the trends, patterns, and research dynamics of FDM-related publications from 2015 to 2024 through a bibliometric approach. The main problem addressed is the lack of systematic insight into the evolution of FDM applications, key contributors, thematic developments, and international collaborations. Data were retrieved from the Scopus database using the keywords “fuzzy delphi” in the title, abstract, or keywords, restricted to journal articles published between 2015 and 2024. The final dataset comprised 1,096 documents. For data processing and analysis, Scopus’s built-in analytics tool was used to obtain basic bibliometric indicators, while OpenRefine was employed for data cleaning and standardization. VOSviewer software was utilized to visualize co-authorship, country collaboration, and keyword co-occurrence networks. The numerical results reveal a significant increase in publication output, especially between 2020 and 2024, with Iran, Taiwan, and Malaysia emerging as the top contributing countries. The subject areas most associated with FDM include social sciences, engineering, business, and environmental science, indicating its wide applicability. Keyword analysis highlights dominant themes such as sustainability, multi-criteria decision-making, and integration with tools like AHP, DEMATEL, and Industry 4.0. The co-authorship network demonstrates strong regional and international collaboration, with notable contributions from countries in Asia and Europe. The results also indicate the presence of a core group of countries and institutions actively publishing and collaborating in this field. In conclusion, this bibliometric analysis provides valuable insights into the development of FDM research over the past decade, identifying leading contributors, emerging themes, and potential.